Mapping the research landscape of food insecurity among tertiary education students worldwide (2002–2023): a scopus database analysis - Olutosin Ademola Otekunrin; Oluwaseun Aramide Otekunrin (Discover Sustainability, 2025)
Abstract One of the most urgent challenges the world faces today is guaranteeing an adequate food supply for the continuously growing global population. Food insecurity (FI) is currently devastating nations globally, particularly African countries, and its impact is also affecting the population of higher education students globally. The high prevalence of FI among higher education students is currently receiving significant attention from policymakers, stakeholders, and researchers. This study aimed to conduct a bibliometric analysis of the literature on FI among higher education students. The literature search was conducted using Scopus database for articles published from 2002 to 2023. The extracted documents were analysed using the bibliometric app on R Studio and VOSviewer software. A total of 496 documents were extracted with publications annual growth rate of 21.7%. United States made the most substantial contribution in terms of the volume of publications, leading authors, collaborations, funding bodies, and institutions. University of California, United States was the most productive institution. The journal Nutrients was the most prolific and highly cited journal. The publication keywords analysis resulted in the formation of four clusters, including keywords like food insecurity, food supply, college students, mental health, COVID-19, and higher education. By providing researchers and stakeholders with a comprehensive overview of existing research on food insecurity among higher education students, this study underscores the importance of translating this knowledge into action. Specifically, it emphasizes the critical need for increased investment in research, funding, and collaboration, with a particular focus on developing countries, alongside targeted mental health support and comprehensive food programmes to effectively alleviate food insecurity.